Solenoid Operated Gear Shifting Mechanism for Two Wheeler - Shitole, Amol; Kotari, Pavan; Magdum, Poonam; Sutar, Omkar; Toraskar, Swapnil; Patil, Prajakta R. (Asian Review of Mechanical Engineering, 2018)
Solenoid operated gear shifting mechanism is mainly designed for the handicapped persons who unable to shift the gears by their foot. The technique used in this gear shifting mechanism consists of solenoid. Solenoid completes one up and down motion called as one stroke. This stroke time depend on supplied voltage and current. According to stroke length and voltage calculation, solenoids are mounted on both sides of gear shifting pedal at ends. By pressing that switch, person easily shifts the gear with the help of foot which is most efficient to handicapped persons.